Techno‐economic assessment of CO2 liquefaction for ship transportation. Issue 6 (25th June 2014) - Zahid, Umer; An, Jinjoo; Lee, Ung; Choi, Seung Phill; Han, Chonghun
Abstract Carbon capture and storage (CCS) is a key technology for addressing global warming by capturing carbon dioxide and storing it somewhere, usually underground. The transportation of CO2 is required since storage sites are not necessarily present near the source sites. Ships can be used for long distance transport of CO2. However, CO2 sources are not always located near the coast; hence onshore transportation may be required in addition to ship for transportation of CO2 from source sites to storage site. Liquefaction is a vital component in ship transportation. In this study, a state‐of‐the‐art CO2 liquefaction processes have been designed by taking CO2 capture facilities into account. The proposed processes require lower liquefaction energy compared to other processes found in the literature. Suitable thermodynamic conditions are required for economical transport of CO2. Therefore, three scenarios each for post‐combustion and pre‐combustion have been studied in order to explore the effect of thermodynamic conditions on the economics of CO2 transport. The considered scenarios are categorized on the basis of liquefaction plant location as: (i) the capture site, liquefaction plant and shipping terminal are located close to each other; (ii) the capture site and liquefaction plant are far from shipping terminal; (iii) the capture site is far from liquefaction plant and shipping terminal. The scenarios results were useful for deciding the optimum liquefaction plant location. Finally, an economic analysis is performed in order to evaluate the feasibility of CO2 transport from source sites to ship loading terminal.© 2014 Society of Chemical Industry and John Wiley & Sons, Ltd